Agglomeration and interregional network effects on European R&D productivity. - Varga, Attila; Pontikakis, Dimitros; Choroafakis, George (PTE KTK Műhelytanulmányok, 2022)
This paper explores the effects of intra-regional agglomeration and interregional networking on the productivity of R&D across EU regions. The paper is based on the spatial econometric modelling framework presented in Varga (2000), and further develops a methodology for estimating the dynamic effects of agglomeration and interregional networks on R&D productivity in regional knowledge creation (measured by patent applications and publications) at the level of EU regions. This empirical modelling framework is applied to classify EU regions into different tiers according to the strengths of their agglomeration effects. These effects are then compared to the network effects of interregional connectedness as reflected in regional participation in the EU Framework Programme for Research. The estimated model is used then for an assessment of the impacts of EU Framework Programme expenditures on technological development and for carrying out policy impact simulations.